If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a + -6 = 16a Reorder the terms: -6 + 4a = 16a Solving -6 + 4a = 16a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-16a' to each side of the equation. -6 + 4a + -16a = 16a + -16a Combine like terms: 4a + -16a = -12a -6 + -12a = 16a + -16a Combine like terms: 16a + -16a = 0 -6 + -12a = 0 Add '6' to each side of the equation. -6 + 6 + -12a = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -12a = 0 + 6 -12a = 0 + 6 Combine like terms: 0 + 6 = 6 -12a = 6 Divide each side by '-12'. a = -0.5 Simplifying a = -0.5
| x+4+3x+2=90 | | -40+5y=10 | | 4v-2=5+7v | | 28=3.5w | | ((28y^6)/(7y^4))^(-2) | | -9x/4=x-11/6 | | x-0.6x=564 | | -32x+4y=12 | | -7/4=x/8 | | x+3=5+x | | -32+4y=12 | | (81)^(-1/3) | | (81)^-1/3 | | 2x-18=19.2 | | 2y+4(y+3)=8y+6(3y+5) | | 47.02-n=-8 | | -x+8y=24 | | e-18/11=17/11 | | 19/7=p-2/7 | | 5/8=-2/x | | g+5/3=11/3 | | m/6-2.9=12.1 | | 5/(-7/3) | | 16+8x=-2x-15 | | 6x+10y=-40 | | 0=x^2+(m+5)x+5m+1 | | (X^-9)/(81y^6z^-12) | | 25=60-5X | | y=x^2+(m+5)x+5m+1 | | x+5=0.84 | | 48/-9x | | 0=x^2+mx+5x+5m+1 |